Comparación del ensayo genexpert MTB/RIF con el frotis convencional y cultivo para el diagnóstico de tuberculosis pulmonar en pacientes con VIH Iquitos 2023 - Baldeon Rios, Jorge Luis (2024)
The objective of the research was to establish a comparison between the diagnostic tests of the GeneXpert MTB/RIF assay with the conventional smear and culture, for the diagnosis of Pulmonary Tuberculosis in Patients with HIV in Iquitos. For this, the quantitative method of retrospective, comparative and cross-sectional observational design was used. The population and sample used were 4,000 GeneXpert MTB/RIF tests applied to patients diagnosed with pulmonary tuberculosis. The technique was the documentary review and the instrument was the results record of TB diagnostic procedures in patients with HIV. The SPSS statistical package version 25.0 was used for data processing and diagnostic accuracy tests were used for comparative analysis. The results show, according to the hierarchical Bayesian analysis between the GeneXpert MTB/RIF and Culture, the GeneXpert MTB/RIF test obtained an average sensitivity of 99.8% (95% CI: 99.5% to 99.9%), while that of the culture was 78.3% (95% CI: 76.6% to 80.0%). In terms of specificity, the Culture test reached a level of 99.9% (95% CI: 99.6% to 100%), while that of the GeneXpert MTB/RIF was 92.9% (95% CI: 91.1% to 94.5%). According to the hierarchical Bayesian analysis between Bacilloscopy and Culture, in terms of sensitivity, the culture obtained an average of 89.4%; while smear microscopy obtained an average of 87.4%. Regarding specificity, the culture obtained a value of 99.9%, while the Baciloscopy obtained 97.1%. In conclusion, it is highlighted that the GeneXpert MTB/RIF test as a diagnostic tool has superior sensitivity, complemented by the high specificity of the Culture test.